Jul 31, 2013 Thread starter #1 F falcios New member Jul 31, 2013 3 How does this formula SPI = EV / PV rearrange to this formula EV = SPI * PV Why does the operation change from multiply to divide? Thanks for the help.

How does this formula SPI = EV / PV rearrange to this formula EV = SPI * PV Why does the operation change from multiply to divide? Thanks for the help.

Jul 31, 2013 Admin #2 M MarkFL Administrator Staff member Feb 24, 2012 13,775 We begin with: \(\displaystyle SPI=\frac{EV}{PV}\) If we next multiply both sides by $PV$, we get: \(\displaystyle SPI\cdot PV=\frac{EV}{PV}\cdot PV=EV\cdot\frac{PV}{PV}=EV\cdot1=EV\)

We begin with: \(\displaystyle SPI=\frac{EV}{PV}\) If we next multiply both sides by $PV$, we get: \(\displaystyle SPI\cdot PV=\frac{EV}{PV}\cdot PV=EV\cdot\frac{PV}{PV}=EV\cdot1=EV\)

Jul 31, 2013 #3 Deveno Well-known member MHB Math Scholar Feb 15, 2012 1,967 - The answer to your "why" question is this: Division is the same as multiplying by a reciprocal, that is: \(\displaystyle \frac{a}{b} = a*\frac{1}{b}\)

- The answer to your "why" question is this: Division is the same as multiplying by a reciprocal, that is: \(\displaystyle \frac{a}{b} = a*\frac{1}{b}\)